Wireless Device with Energy Management for Closed-Loop Deep Brain Stimulation (CLDBS) - Matheus Nordi, Tiago; Augusto Ginja, Gabriel; Gounella, Rodrigo; Talanoni Fonoff, Erich; Colombari, Eduardo [UNESP]; Moreira, Melkzedekue M. Alcântara; Afonso, Jose A.; Monteiro, Vitor; Afonso, Joao L.; Carmo, João Paulo (MDPI, 2023)
Deep brain stimulation (DBS) is an effective and safe medical treatment that improves the lives of patients with a wide range of neurological and psychiatric diseases, and has been consolidated as a first-line tool in the last two decades. Closed-loop deep brain stimulation (CLDBS) pushes this tool further by automatically adjusting the stimulation parameters to the brain response in real time. The main contribution of this paper is a low-size/power-controlled, compact and complete CLDBS system with two simultaneous acquisition channels, two simultaneous neurostimulation channels and wireless communication. Each channel has a low-noise amplifier (LNA) buffer in differential configuration to eliminate the DC signal component of the input. Energy management is efficiently done by the control and communication unit. The battery supports almost 9 h with both the acquisition and stimulation circuits active. If only the stimulation circuit is used as an Open Loop DBS, the battery can hold sufficient voltage for 24 h of operation. The whole system is low-cost and portable and therefore it could be used as a wearable device.
Keywords: closed-loop deep brain stimulation (CLDBS); energy management; implantable devices; internet of things (IoT); neurostimulation